On asymptotic normality of the least square estimators of an infinite-dimensional parameter - Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Asymptotic properties of the estimators of an infinite-dimensional parameter are studied.